2012
DOI: 10.1155/2012/265657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Weight and Molar Ratio of Dextran on Self‐Assembly of Dextran Stearate Polymeric Micelles as Nanocarriers for Etoposide

Abstract: Amphiphilic polymer surfactants are composed of hydrophilic and hydrophobic polymers and are widely used in targeted drug delivery. The purpose of this study was the evaluation of the effect of molecular weight and molar ratio of dextran on physicochemical properties of dextran stearate polymeric micelles. Dextran stearate was synthesized by acylation of dextran with stearoyl chloride. Etoposide loaded polymeric micelles were prepared by dialysis method. The resulting micelles were evaluated for particle size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(22 reference statements)
2
11
0
Order By: Relevance
“…The method reported in our previous work was used for this synthesis [ 15 ]. Briefly, 1 g of dextran molecular weight (Mw) 6000 (0.166 mmol) was added to 20 mL DMF and stirred at 120°C for 2 h under nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method reported in our previous work was used for this synthesis [ 15 ]. Briefly, 1 g of dextran molecular weight (Mw) 6000 (0.166 mmol) was added to 20 mL DMF and stirred at 120°C for 2 h under nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Stearate grafted dextran has been synthesized by Du et al [ 14 ] via an esterification reaction and is used to carry doxorubicin to nude mice bearing A549 human lung adenocarcinoma. The effect of molecular weight and molar ratio of dextran on self-assembly of dextran stearate polymeric micelles was further studied by Varshosaz et al [ 15 ]. In vitro cytotoxicity tests showed good toxic effect against drug-sensitive tumor cells while the polymer itself was nontoxic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be related to the different stereo packing structures of the metal complexes. In addition, these results will expand the research areas for the special amphiphiles without alkyl chain and give some clues to prepare new nanomaterials and nanocomposites [35][36][37][38].…”
Section: Discussion Of Assemblymentioning
confidence: 82%
“…A review of this was reported by Goodarzi et at [257]. In recent years, DEX nanocarriers for cancer therapy have been developed based on the modification of DEX to obtain amphiphilic derivatives that self--assemble into micellar or nanoparticulate systems.Varshosaz et al[315] prepared DEX stearate PM as carriers of etoposide. The composition was tuned by changing MW of DEX and molar ratio of stearate.…”
mentioning
confidence: 99%